The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3892/ijmm.2010.582
|View full text |Cite
|
Sign up to set email alerts
|

Tiny percutaneous needle biopsy: An efficient method for studying cellular and molecular aspects of skeletal muscle in humans

Abstract: Abstract. Needle biopsy is widely used to obtain specimens for physiological, anatomical and biochemical studies of skeletal muscle (SM). We optimized a procedure which we termed tiny percutaneous needle biopsy (TPNB), to efficiently gather good numbers of human satellite cells and single dissociated fibers for the functional study of skeletal muscle; these samples permit isolation of high-quality RNA and sufficient amounts of proteins to allow molecular analysis. Moreover, TPNB showed a clear advantage in tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…Human muscle samples were derived from Vastus Lateralis muscle biopsies using the tiny percutaneous needle biopsy (TPNB) (Pietrangelo et al., ). Young and elderly healthy untrained subjects underwent voluntary biopsies.…”
Section: Methodsmentioning
confidence: 99%
“…Human muscle samples were derived from Vastus Lateralis muscle biopsies using the tiny percutaneous needle biopsy (TPNB) (Pietrangelo et al., ). Young and elderly healthy untrained subjects underwent voluntary biopsies.…”
Section: Methodsmentioning
confidence: 99%
“…d′Annunzio' University of Chieti–Pescara (protocol numbers: 1233/06 COET, dated 25 July 2006; 1884 COET, dated 15 May 2009; and 1634/08 COET, dated 24 June 2008). 39 The inclusion criteria were as follows: normal ECG and blood pressure; lack of bone and joint disorders, or metabolic (that is, diabetes) and/or cardiovascular diseases. The exclusion criteria were as follows: the presence of metabolic and/or cardiovascular diseases, evidence of hereditary or acquired muscular disorders, diagnosis of respiratory disorders or psychiatric problems.…”
Section: Methodsmentioning
confidence: 99%
“…We further obtained three small biopsy samples from the vastus lateralis (VL) muscle from 32–66-year-old male healthy volunteers (indicated as M32, 32 years old; M33, 41 years old; M34, 66 years old, respectively) using the TPNB procedure as described in our previous study [Pietrangelo et al (1)]. The study was approved by the Ethics Committee of the University of Chieti-Pescara (approval protocol no.…”
Section: Methodsmentioning
confidence: 99%
“…We recently described a procedure for human muscle biopsy that we termed tiny percutaneous needle biopsy (TPNB) and we demonstrated that it is an excellent method for obtaining human skeletal muscle specimens with the least trauma for the patient (1). The classically and commonly used needle biopsy technique is needle aspiration biopsy (NAB), using a Bergstrom needle (2,3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation